The Correlation Between Self-Efficacy and Speaking Performance of the Eleventh-Grade Students at SMAN 1 Palangka Raya - Christy Givency (The Study Program of English Education of Palangka Raya University, 2023)
Speaking is a common English skill which is still difficult to master in Indonesia. Especially in secondary school contexts, many students cannot use English for communication functions although they have studied it for several years. As the modern era demands the need of communication skills, this research was initiated to discover whether there is a correlation between self-efficacy and students’ speaking performance to help them improve their speaking skill. The study was conducted with a sample of 40 high school students from class XI MIPA 2 of SMAN 1 Palangka Raya. To collect the data, self-efficacy questionnaire, speaking test, and documentation of students’ latest speaking scores and teacher’s notes of students’ activeness in English class were used. The data then was calculated and analyzed using IBM SPSS Statistics 25 Program. It was found there was a weak correlation (r-count = 0.333) between the two variables. The level of students’ self-efficacy was moderate, but their level of speaking ability was high. Therefore, the study concluded self-efficacy has little or no direct effect on students’ speaking performance. It is suggested that English teachers can continue to improve students’ speaking skill and further research is conducted to find more evidence of this phenomenon.